2006
DOI: 10.1021/ac0613479
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Bilayer Formation by Contacting Monolayers in a Microfluidic Device for Membrane Protein Analysis

Abstract: Artificial planar lipid bilayers are a powerful tool for the functional study of membrane proteins, yet they have not been widely used due to their low stability and reproducibility. This paper describes an accessible method to form a planar lipid bilayer, simply by contacting two monolayers assembled at the interface between water and organic solvent in a microfluidic chip. The membrane of an organic solvent containing phospholipids at the interface was confirmed to be a bilayer by the capacitance measurement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
384
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 431 publications
(393 citation statements)
references
References 32 publications
7
384
0
Order By: Relevance
“…Since the maximum surface area for the lipid bilayer is the size of the aperture (100 m X 85 m), we obtain a specific membrane capacitance of at least 0.4 µF.cm -2 . Considering the lipid bilayer surface area measured with confocal microscopy, we estimate a specific membrane capacitance of ~ 0.5 µF.cm -2 , which is within capacitance values previously reported for DPhPC lipid membranes [29][30][31] , indicating little or no residual decane in the bilayer membrane, and remarkably less than for a bilayer at a droplet interface 30 .…”
Section: Electrical Measurements Of Lipid Bilayerssupporting
confidence: 85%
“…Since the maximum surface area for the lipid bilayer is the size of the aperture (100 m X 85 m), we obtain a specific membrane capacitance of at least 0.4 µF.cm -2 . Considering the lipid bilayer surface area measured with confocal microscopy, we estimate a specific membrane capacitance of ~ 0.5 µF.cm -2 , which is within capacitance values previously reported for DPhPC lipid membranes [29][30][31] , indicating little or no residual decane in the bilayer membrane, and remarkably less than for a bilayer at a droplet interface 30 .…”
Section: Electrical Measurements Of Lipid Bilayerssupporting
confidence: 85%
“…[1][2][3] With phospholipid molecules as surfactants, droplet-droplet contact leads to the expulsion of the interdroplet oil film and the formation of an interdroplet lipid bilayer, 4,5 as illustrated in Fig. 1.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we demonstrated that submicrolitre aqueous droplets submerged in an apolar liquid containing lipid can be tightly connected by means of lipid bilayers [1][2][3][4][5] to form networks [4][5][6] . Droplet interface bilayers have been used for rapid screening of membrane proteins 7,8 and to form asymmetric bilayers with which to examine the fundamental properties of channels and pores 9 .…”
mentioning
confidence: 99%